The centralization and standardization of student services in Universitas Terbuka - Chanif Nurcholis; Sri Wahyu Kridasakti; Hardianto, Hanif (Technium Social Sciences Journal, 2024)
Universitas Terbuka (UT) now a days is applying the centralization and standardization model on its student service management system. Those both administrative and academic services are handled directly by t he Rectorate office and the working units under it. Student administrative services include admission, registration, tutoring the Modul-Base of course subject matter, exam-schedules determination, exam-results announcement, grader-transcripts printing and graduation ceremonies. Academic services involve curriculum establishment, subject course material settlement, tutorial services, remedial teaching, learning assessment, and academic judisium. The objectives of managerial centralization and standardization are at least assuring the achievement of managerial efficiency and effectivity. However, in the practical terms the midle line and operating core bussiness services apperently could not resolve problems in quick and effective manner, when students asked for help due to the problems of delivered administrative and academic services. The research question was "what is the impact of centralized and standardized of student service management system to the UT overall services performance?". The method used was a case-study, and the data were taken through series of document review, observation technique and interviews. The data were analyzed descriptively qualitative using MPFAAC technique. The study concluded that the student service managerial centralization and standardization brought about the inability of the midle line and operating core bussiness services from doing any job creativity, innovation, and responsivity.